The Effectiveness Of Using Word Cards As A Media On Learning Vocabulary For The Tenth Graders Of Ma Nw Sikur - Ahmad Zuhri rosyidi; Atika Salman Paris (Lembaga Riset Ilmiah, 2022)
Word cards are exactly the right media for students to enrich students’ vocabulary mastery. To prove this argumentation this study was focus on using word cards on students’ achievement in learning vocabulary in classroom. This study used an experimental design and to collect the data, the present researcher used multiple choices instrument (vocabulary test) to get students’ score in learning vocabulary. In analyzing data, the present researcher used t-test to find out the effectiveness of the word card in teaching vocabulary. The result of analysis data that the t-test was 0.74 and t-table was 0.44 with level of significance (95%) from the total of sample was twenty students. It means t-test was higher than t-table (0.74 0.44). Thus, mean alternative hypothesis (Ha) was accepted, and the null hypothesis (Ho) was rejected. This founding means that there was a significantly effective of using word cards on students’ achievement in learning vocabulary for the tenth grade of MA NW Sikur in the school year 2021-2022.